A case of type 2 diabetes mellitus with metformin‐associated lactic acidosis initially presenting the appearance of a sulfonylurea‐related hypoglycemic attack. Issue 1 (3rd August 2016) - Nishihama, Kota; Maki, Kanako; Okano, Yuko; Hashimoto, Rei; Hotta, Yasuhiro; Uemura, Mei; Yasuma, Taro; Suzuki, Toshinari; Hayashi, Toyomi; Ishikawa, Eiji; Yano, Yutaka; Gabazza, Esteban C.; et al.
Abstract : Case: A 64‐year‐old Japanese woman with diabetes mellitus was admitted for hypoglycemia. Her diabetes had been under good control with glimepiride, voglibose, exenatide, and metformin for a few years. Although overt proteinuria was observed, the serum creatinine values were within normal range during the routine outpatient follow‐up. Hypoglycemic attack caused by glimepiride and loss of appetite by urinary tract infection were diagnosed. Then, metformin‐associated lactic acidosis with acute renal failure caused by dehydration was detected. Outcome: Her condition was improved by continuous veno‐venous hemodiafiltration and hemodialysis, known to be useful to remove metformin. Conclusion: We reported a case of metformin‐associated lactic acidosis with hypoglycemia during routine treatment of diabetes that was successfully rescued by early renal replacement therapy.